Atomic Interface‐Exciting Catalysis on Cobalt Nitride‐Oxide for Accelerating Hydrogen Generation. Issue 22 (4th May 2022) - Guan, Shuyan; Liu, Yanyan; Zhang, Huanhuan; Wei, Huijuan; Liu, Tao; Wu, Xianli; Wen, Hao; Shen, Ruofan; Mehdi, Sehrish; Ge, Xianghong; Wang, Chengming; Liu, Baozhong; et al.
Abstract: The rational design of the interface structure between nitride and oxide using the same metallic element and correlating the interfacial active center with a determined catalytic mechanism remain challenging. Herein, a Co4 N‐Co3 O4 interface structure is designed to determine the effect of interfacial active centers on hydrogen generation from ammonia borane. An unparalleled catalytic activity toward H2 production with a turnover frequency up to 79 min −1 is achieved on Co4 N‐Co3 O4 @C catalyst for ten recycles. Experimental analyses and theoretical simulation suggest that the atomic interface‐exciting effect (AieE) is responsible for the high catalytic activity. The Co4 N‐Co3 O4 interface facilitates the targeted adsorption and activation of NH3 BH3 and H2 O molecules to generate H * and H2 . The two active centers of Co(N) * and Co(O) * at the Co4 N‐Co3 O4 interface activate NH3 BH3 and H2 O, respectively. This proof‐of‐concept research on AieE provides important insights regarding the design of heterogeneous catalysts and promotes the development of the nature and regulation of energy chemical conversion. Abstract : An unparalleled activity toward H2 production from ammonia borane hydrolysis is achieved with a turnover frequency (4716 h −1 ) on a Co4 N‐Co3 O4 interfacial catalyst. An atomic interface‐exciting effect (AieE) is responsible for the origin of catalytic activity via an activation of ammonia borane and water molecules on two active centers of Co(N) * and Co(O) *, respectively.